The Boss’s Long Arm: The Differential Impact of Authoritarian and Benevolent Leadership on Spousal Family Satisfaction - Yao, Lei; Xu, Minya; Pellegrini, Ekin K. (Frontiers in Psychology, 2021)
The extant studies on leadership are replete with employee, coworker, and leader outcomes, however, research is still nascent on leadership’s crossover into employees’ family members’ lives. To examine leadership’s impact on the work–family interface, we draw on conservation of resources theory and crossover theory and investigate how authoritarian leadership and benevolent leadership affect spousal family satisfaction. We examine the mediating influence of work-family conflict (WFC) and work-family facilitation (WFF), and the moderating impact of spouses’ need for control. Our model was tested with multisource, mutiwave data from 207 Chinese married dyads. The results suggest that, as expected, the positive relationship between benevolent leadership and spousal family satisfaction is fully mediated by WFF, and the negative relationship between authoritarian leadership and spousal family satisfaction is fully mediated by WFC. Findings further suggest that the negative relationship between employee WFC and spousal family satisfaction is stronger for spouses with a higher need for control. Thus, authoritarian leadership, through its negative influence on WFC appears to be universally detrimental for spousal family satisfaction, however even more so for spouses with a higher need for control. These results underscore the importance of acknowledging leadership’s impact at work reaching far beyond the job incumbent.